Capacitance-based sensor with layered carbon-fiber reinforced polymer and titania-filled epoxy. (1st November 2019) - Yan, Jin; Downey, Austin; Chen, An; Laflamme, Simon; Hassan, Sammy
Abstract: Advances in intelligent infrastructure can be achieved through the use of novel materials for increased system-level efficiency and multifunctionality. Carbon Fiber-Reinforced Polymer (CFRP) has been widely used in strengthening, rehabilitating, and retrofitting of existing structures because of its speed of deployment, low maintenance requirement, and high strength-to-weight ratio. In this work, the authors propose a novel method to augment CFRP with self-sensing capabilities. The sensor consists of two CFRP layers separated by a titania-filled epoxy dielectric layer, therefore forming a parallel plate capacitor. Sensing capability can be achieved through variations in the sensor's capacitance provoked by strain, therefore providing an additional function that could be leveraged for structural health monitoring and structural health management purposes. Comprehensive testing, including (1) sensing properties on sensors with and without titania-doped epoxy and (2) electromechanical test on tension specimens subjected to both static and dynamic loading, was conducted. The test results show that doping the titania filler within the epoxy matrix can improve the sensor's sensitivity, and that the sensor's signal increases linearly with increasing strain. A static gauge factor of 0.92 was obtained, and the dynamic gauge factor characterized under 0.25, 0.5, and 1 Hz. It is also found that CFRP can be used as a self-sensing material without affecting its mechanical properties.